Evaluasi bimbingan karakter : Bimbingan karakter - Ratna Dewi; Septia Amalia; Ulwahidah, Siti Putri Annisa (Cakrawala Pedagogik, 2024)
This research discusses the evaluation of the character guidance program at SDN 3 Bojongmenteng. The aim of this research is to determine the quality and effectiveness of character guidance programs in schools. The research used was descriptive qualitative techniques. Based on the results of research that has been carried out regarding the implementation of the evaluation of the character guidance program for SDN 3 Bojongmenteng students using interview techniques as a whole, it can be concluded that the evaluation of the character guidance program is in the good category. With these good results, class teachers at SDN 3 Bojongmenteng must remain consistent in correcting existing deficiencies so that the results obtained can be maximized and in line with what is expected.